THE INFLUENCE OF OCCUPATIONAL SAFETY SOCIALIZATION ON REDUCING THE INCIDENCE OF WORK ACCIDENTS AT THE KLARI KARAWANG COMMUNITY HEALTH CENTER - Jumaedi, Jumaedi; Chaerani Tri Yuliana; Wieke Widhiantika; Yasin Azhari; Muhidin, Muhidin; Wendi Darmawan (Bajang Institute, 2023)
Work accidents in healthcare facilities, such as community health centers (Puskesmas), pose a serious problem that affects the safety and well-being of healthcare workers. This study aims to evaluate the impact of occupational safety awareness programs on reducing the incidence of work accidents at Puskesmas Klari, Karawang. The research uses a quantitative approach with an analytical survey design, involving 50 healthcare workers as respondents using a total sampling technique. Data were collected through validated and reliable questionnaires and analysed using logistic regression to determine the impact of safety awareness on the occurrence of work accidents. The results show that safety awareness programs significantly influence the increase in healthcare workers' awareness, which is followed by a decrease in work accident rates. The